Change Management And Development At PT. Jasamarga Belmera Branch TBK - Fauzan, Muhammad (Jurnal Fokus Manajemen, 2024)
Companies operating in a changing environment must be able to manage change well in order to remain relevant and competitive. PT Jasamarga Cabang Belmera Tbk (Jasamarga Belmera) is a company engaged in toll road management services in Indonesia. In the face of industry development and increasingly complex market demands, Jasamarga Belmera needs to implement effective change management and development to achieve its business objectives. This abstract discusses the practice of change management and development implemented by PT Jasamarga Belmera Branch Tbk. in facing the dynamics of the company and industry.